Risk analysis and contract management for Public Private Partnership projects in Egypt - Badran, Yosr (AUC Knowledge Fountain, 2013)
In the light of the current political and economic conditions in Egypt, Public Private Partnership projects appear as an effective solution in order to help the government in enhancing its infrastructure, utilities and services using the technical skills and capabilities of the private partner. Although Public Private Partnerships are used all over the world, they can be of particular importance in developing countries which seek a quick and effective in improving its projects. Accordingly, Public Private Partnerships started to be used in Egypt and there are several projects under study for future implementation. The two key success factors for PPP projects are a proper risk allocation and a suitable contract so that the risks are adequately covered and are properly assigned to the party who is the best at managing them. In this research, the top 59 risk factors that affect PPP projects are identified from the Literature Review and are grouped into several critical risk groups and included in a questionnaire which is distributed among a number of experts (25 experts) who worked internationally and in the Egyptian Market. The results of the survey showed that the top 26 risks are from the following groups: Financial and Macroeconomic risk group, Commercial risk group, Legal risk group, Political risk group, Regulatory risk group, Government maturity risk group, Technical risk group, Production risk group, and Unforeseen risk group. An attempt for mapping the identified risks and the risk allocation identified in the survey is done to contract clauses of two PPP projects contracts where the risk allocation is defined clearly in the clause (public private or both). In some cases, the risk allocation according to the survey results was perfectly conforming to the risk allocation according to the real case contracts such as in the case of the Performance Security risk, the Permits risk, the Unforeseen Geotechnical conditions risk and the Latent Defect risk. In other cases, the risk allocation according to the survey results was not conforming to the risk allocation according to the real case contracts such as in the case of Nationalization/expropriation risk and the Government Corruption risk. In addition, a prototype for Risk Decision Support System for the top ranked risks in the survey was developed using Crystal Ball software in order to determine the overall severity and the overall contingency percentage of the project. Finally the top risks are compared to the critical risks obtained from the previous studies in China, India and Singapore and the top risks identified were conforming to a great extent.